Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes with an MT-TL1 m.3243A>G point mutation: Neuroradiological features and their implications for underlying pathogenesis - Zheng, Helin; Zhang, Xuemei; Tian, Lu; Liu, Bo; He, Xiaoya; Wang, Longlun; Ding, Shuang; Guo, Yi; Cai, Jinhua (Frontiers in Neuroscience, 2023)
Objective: Mitochondrial encephalomyopathy with lactic acidosis and stroke‑like episodes (MELAS) is one of the most common inherited mitochondrial disorders. Due to the high clinical and genetic heterogeneity of MELAS, it is still a major challenge for clinicians to accurately diagnose the disease at an early stage. Herein, we evaluated the neuroimaging findings of MELAS with an m.3243A>G mutation in MT‑TL1 and analyzed the possible underlying pathogenesis of stroke-like episodes. Materials and methods: Fifty-nine imaging studies in 24 patients who had a confirmed genetic diagnosis of m.3243A>G (MT-TL1; tRNALeu) associated with MELAS were reviewed in our case series. The anatomic location, morphological features, signal/intensity characteristics and temporal evolution of lesions were analyzed on magnetic resonance imaging (MRI) and computed tomography (CT) images. The supplying vessels and metabolite content of the lesions were also evaluated by using MR angiography (MRA)/CT angiography (CTA) and MR spectroscopy (MRS), respectively. Results: The lesions were most commonly located in the posterior brain, with 37 (37/59, 63%) in the occipital lobe, 32 (32/59, 54%) in the parietal lobe, and 30 (30/59, 51%) in the temporal lobe. The signal characteristics of the lesions varied and evolved over time. Bilateral basal ganglia calcifications were found in 6 of 9 (67%) patients who underwent CT. Cerebral and cerebellar atrophy were found in 38/59 (64%) and 40/59 (68%) patients, respectively. Lesion polymorphism was found in 37/59 (63%) studies. MRS showed elevated lactate doublet peaks in 9/10 (90%) cases. MRA or CTA revealed that the lesion-related arteries were slightly dilated compared with those of the contralateral side in 4 of 6 (67%) cases. Conclusions: The imaging features of MELAS vary depending on the disease stage. Polymorphic lesions in a single imaging examination should be considered a diagnostic clue for MELAS. Stroke-like episodes may be involved in a complex pathogenetic process, including mitochondrial angiopathy, mitochondrial cytopathy, and neuronal excitotoxicity.